Pengaruh Mesenchymal Stem Cell (MSC) pada Penyakit Jantung Bawaan dengan Hipertensi Pulmonal - Benny Afriansyah; Kino (Fakultas Kedokteran, Universitas Andalas, 2026)
Background: Congenital heart disease (CHD) with pulmonary hypertension is a progressive condition characterized by vascular remodeling and pulmonary endothelial dysfunction, which leads to increased pulmonary vascular resistance and right ventricular failure. Mesenchymal stem cells (MSCs) represent a potential therapeutic approach for regenerating pulmonary endothelial and vascular cells in patients with pulmonary hypertension. MSCs have the capacity to differentiate into various cell types and secrete paracrine factors that promote tissue Repair. Objective: This study aims to critically review the available scientific evidence on the impact of Mesenchymal Stem Cell (MSC) therapy on pulmonary hypertension associated with congenital heart disease, focusing on therapeutic efficacy, underlying mechanisms of action, and safety profile as a potential clinical intervention. Methods: A narrative review of the literature published between 2007 and 2025 was performed. Relevant studies were identified through systematic searches of PubMed, Scopus, ScienceDirect, and Google Scholar using the following keywords: “congenital heart disease,” “pulmonary hypertension,” and “Mesenchymal Stem Cell.” Results: Studies have demonstrated that MSC therapy can improve right ventricular hemodynamics through adaptive anti-inflammatory and regenerative mechanisms. However, further research is necessary to establish the long-term safety, optimal dosage, and molecular mechanisms underlying the widespread application of MSC therapy, particularly in patients with CHD and pulmonary hypertension. Conclusion: Mesenchymal Stem Cells (MSCs) demonstrate promising therapeutic potential in pulmonary hypertension associated with congenital heart disease through mechanisms including homing capacity, anti-inflammatory effects, and vascular–cardiac regeneration. Therefore, MSCs may emerge as an effective adjuvant or alternative therapeutic option in the future, although further clinical validation is still required.